Transformations in the Livelihood Activities of Hlengwe People of the South-East Lowveld of Zimbabwe, 1890–2014 - Chisi, Taderera Hebert (Springer, 2022)
The Hlengwe people of the south-east Lowveld of Zimbabwe are commonly known as Shangaan/‘Machangana’ or Tsonga. Their traditional livelihood activities such as hunting, fishing, gathering, agriculture and trade were unique to the extent that they could be easily used as features of identity differentiation between the Hlengwe and neighbouring ‘ethnic others’ such as Duma and Karanga. However, the uniqueness of some of these activities has diminished over the years. This chapter is premised on the argument that the livelihood activities of ethnic communities are not static but shift with time in response to changes in the social, political and physical environment. In this context, it analyses the transformation of the Hlengwe livelihood activities from 1890 (the time of British colonialism) to the twenty-first century. Overall, the Hlengwe livelihood activities morphed over the years to a point where, by the early twenty-first century, ethno-commerce or commodification of marketable features of identity such as cultural symbols, art and craft and living cultures remained the main livelihood activity which still reflected Hlengwe ethnicity more than any other activities in the modern multi-ethnic society of the south-east Lowveld.